Structure of disturbed mixed-dipterocarp forest at Mount Jagoi community forest, Bau :|ban assessment 24 years after logging - Esther Tiffany, Redim (Universiti Malaysia Sarawak, UNIMAS, 2012)
Forest Inventory was carried out at Mount Jagoi, Bau, between July 2011 and April 2012 to assess the condition of the forest stand 24 years after logging and to compare the stand structure with the structure of undisturbed forest. Sample plots of 10 m x 40 m were randomly chosen in a logged-over mixed Dipterocarp Forest and Kerangas Forest at several locatities within the Gunung Jagoi community forest. Results indicate that the number of taller trees was higher in the undisturbed mixed-dipterocarp forests which were at the Sobak Ayak Girituong, Otak Bowang, and Bikubu Taub compared to the logged-over area at Spolup Hill and the kerangas forest at Po Aub Hill. The most abundant species found in undisturbed forest is Cinnamomum sp. while in logged-over forest, Shorea sp. and Artocarpus odoratissimus were the most abundant. Hevea brasiliensis is the most abundant species in kerangas forest. The highest above ground biomass per hectare was found in the undisturbed forest with the value 9612 metric ton/ha while the lowest was found in kerangas forest with the value 1502 metric ton/ha.